Risk Factors Associated with Gestational Diabetes Mellitus Among Pregnant Women - Eshrak Bin Ramadan,; Nadia Alhamdi,; Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2024)
Gestational diabetes mellitus (GDM) represents 84% of hyperglycemia during pregnancy throughout the world. Moreover, being black is a risk factor to develop the disease. Our objective was to determine the prevalence and the associated factors of GDM in Tripoli. A descriptive cross-sectional study was conducted over the period from March to April 2024. We have selected 3 diagnostic laboratories inside Tripoli to collect the data. Pregnant women were enrolled at each center where we had stayed for a week. Majority of participants 42.5% were in the age ≥ 35 years, and the lowest 11.5% were from the age of 20-24 years. The mean body mass index (BMI) was higher 60.5% for those with ≥25 and was lower 39.5% for those ≤25. For gestational ages, most of participants 48.5% were between 24-28 gestational week, while the minority 11.5% were within 24 gestational weeks. The highest percentage 42.5% regarding the parity was for pregnant with Pauciparous (1-4), and minority of participants 92.5% had history for GDM. Careful surveillance is required for these pregnancies in high-risk units for early detection and treatment of possible complications, in order to try to reduce maternal and neonatal morbidities. Further prospective studies among these high-risk populations with gestational diabetes should investigate the efficacy of possible surveillance programs. يمثل داء السكري خلال فترة الحمل 84% من حالات ارتفاع السكر في الدم أثناء الحمل في جميع أنحاء العالم. علاوة على ذلك، فإن لون البشرة السمراء يعد عامل خطر للإصابة بالمرض. كان هدفنا هو تحديد مدى انتشار داء السكري خلال فترة الحمل والعوامل المرتبطة به في طرابلس. تم إجراء دراسة وصفية خلال الفترة من مارس إلى أبريل 2024. وقد اخترنا 3 مختبرات تشخيصية داخل طرابلس لجمع البيانات. تم تسجيل النساء الحوامل في كل مركز أقمنا فيه لمدة أسبوع. كانت أعمار غالبية المشاركين 42.5% ≥ 35 عامًا، وأدنى 11.5% كانوا تتراوح أعمارهم بين 20-24 عامًا. كان متوسط مؤشر كتلة الجسم أعلى بنسبة 60.5% لأولئك الذين لديهم ≥25 وكان أقل بنسبة 39.5% لأولئك الذين لديهم ≥25. بالنسبة لأعمار الحمل، كان معظم المشاركين 48.5% بين 24-28 أسبوع حمل، بينما الأقلية 11.5% كانوا ضمن 24 أسبوع حمل. أعلى نسبة 42.5% فيما يتعلق بالتكافؤ كانت للحوامل مع Pauciparous (1-4)، وأقلية من المشاركين 92.5% لديهم تاريخ داء السكري خلال فترة الحمل. يلزم إجراء مراقبة دقيقة لحالات الحمل هذه في الوحدات عالية الخطورة للكشف المبكر عن المضاعفات المحتملة وعلاجها، من أجل محاولة الحد من أمراض الأمهات والأطفال حديثي الولادة. ينبغي إجراء المزيد من الدراسات المستقبلية بين هؤلاء السكان المعرضين لخطر الإصابة بسكري الحمل للتحقق من فعالية برامج المراقبة المحتملة